An Unkind Cut. - Kell, C.F. ?; Morgan ? (Kell, C.F. ?, 1885)
Scholarly notes may be added at a later date.
[The Whithall Review?] November 5th. 1885.
1 print : b&w
Keywords: Caricatures; Cartoons; Liberalism; Great Britain -- Politics and government -- 1837-1901; Bagpipers